2020
DOI: 10.1101/2020.06.07.20124636
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamics of IgG seroconversion and pathophysiology of COVID-19 infections

Abstract: We report dynamics of seroconversion to SARS-CoV-2 infections detected by IgG ELISA in 177 individuals diagnosed by RT-PCR. Longitudinal analysis identifies 2-8.5% of individuals who do not seroconvert even weeks after infection. They are younger than seroconverters who have increased co-morbidity and higher inflammatory markers such as C-Reactive Protein. Higher antibody responses are associated with non-white ethnicity. Antibody responses do not decline during follow up almost to 2 months. Serological assays… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 17 publications
3
50
0
3
Order By: Relevance
“…Older adults • Five studies found no association between antibody response and age, for both antibody positivity 147 or IgM/IgG titre. 21,58,148,167 • One study found that 'older' patients were more likely to seroconvert, 153 and concentration of IgG was related to age. 34…”
Section: Agementioning
confidence: 99%
See 1 more Smart Citation
“…Older adults • Five studies found no association between antibody response and age, for both antibody positivity 147 or IgM/IgG titre. 21,58,148,167 • One study found that 'older' patients were more likely to seroconvert, 153 and concentration of IgG was related to age. 34…”
Section: Agementioning
confidence: 99%
“…Three studies report an association between co-morbidities and seroconversion or antibody positivity, 64,153 with one finding immunocompromised individuals developed a lower response. 154…”
mentioning
confidence: 99%
“…CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity. (which was not certified by peer review) preprint The copyright holder for this this version posted September 27, 2020. ; https://doi.org/10.1101/2020.09.25.20183459 doi: medRxiv preprint close to the cut-off, when the reference venous blood was positive and capillary blood was indeterminate (Adams et al, 2020;Staines et al, 2020).…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…The copyright holder for this this version posted September 27, 2020. ; https://doi.org/10.1101/2020.09.25.20183459 doi: medRxiv preprint sensitivity (21% to 92%), that was significantly inferior to ELISAs performed on venous blood (Flower et al, 2020). Studies have shown high sensitivity of ELISAs for the detection of SARS-CoV-2 antibodies in venous blood (Adams et al, 2020;Lisboa Bastos et al, 2020;Staines et al, 2020). Capillary blood is a well-established specimen in ELISA diagnostics but it is yet to be evaluated in SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…(6,7) Similarly, with SARS-CoV-2, immune responses associated with the natural course of SARS-CoV-2 viral infection suggest that anti-Spike IgG antibody responses are usually weak (except for the fortunately less frequent severe cases) and their durability lasts for up to 3 months, in most cases, or decline by up to 70% within this time period. (8) In addition, 2-9% of individuals do not seroconvert even 2 months after infection with SARS-CoV-2, (9) suggesting that individuals reached immunity using another arm of the adaptive immune system, T cells. Indeed, it could be concluded that virtually all subjects with a history of SARS-CoV-2 infection mount T cell responses against the virus, including seronegatives and subjects with severe disease.…”
Section: Introductionmentioning
confidence: 99%